Problems of development of innovative activity in the Republic of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
There are a lot of projects and strategies are accepted tp develop Kazakhstan’sinnovative activity, innovative infrastructure is carried out. Alot of expeditions are taking place, articles are written and developed.But this questions cannot be solved yet, because it hard to bind businesseith science. The word science frightens and mistrusts businessman, youngpeople doesn’t have will to do science. One way to atract young peopleto science is to build innovative activity of technopark structure and toinvolve students and magistrants to its managing process, to supply themwith workplace connected with it and to improve the science status.The main aim of innovative process is to improve economic, sciencetechnic,ecological and social state of the country by entering innovation,therefore it will inprove the competetiveness of the country. NowadaysKazakhstan’s economic state has big opportunity to carry out technologicalinnovations,for example to make tools that are neccessary to producemachine and to do the mining and agricultural production, to find andunite new methods to save the agricultural production.
Keywords: Innovation; innovative activity; innovative infrastructure; innovation strategy.